Rationale and design of the Kanyini guidelines adherence with the polypill (Kanyini-GAP) study: a randomised controlled trial of a polypill-based strategy amongst Indigenous and non Indigenous people at high cardiovascular risk - Usherwood Tim; Rodgers Anthony; Wade Vicki; Weeramanthri Tarun; Tonkin Andrew; Stewart Greg; Ring Ian; Jan Stephen; Hayman Noel; Eades Sandra; Brown Alex; Patel Anushka; et al. (BMC, 2010)
Abstract Background The Kanyini Guidelines Adherence with the Polypill (Kanyini-GAP) Study aims to examine whether a polypill-based strategy (using a single capsule containing aspirin, a statin and two blood pressure-lowering agents) amongst Indigenous and non-Indigenous people at high risk of experiencing a cardiovascular event will improve adherence to guideline-indicated therapies, and lower blood pressure and cholesterol levels. Methods/Design The study is an open, randomised, controlled, multi-centre trial involving 1000 participants at high risk of cardiovascular events recruited from mainstream general practices and Aboriginal Medical Services, followed for an average of 18 months. The participants will be randomised to one of two versions of the polypill, the version chosen by the treating health professional according to clinical features of the patient, or to usual care. The primary study outcomes will be changes, from baseline measures, in serum cholesterol and systolic blood pressure and self-reported current use of aspirin, a statin and at least two blood pressure lowering agents. Secondary study outcomes include cardiovascular events, renal outcomes, self-reported barriers to indicated therapy, prescription of indicated therapy, occurrence of serious adverse events and changes in quality-of-life. The trial will be supplemented by formal economic and process evaluations. Discussion The Kanyini-GAP trial will provide new evidence as to whether or not a polypill-based strategy improves adherence to effective cardiovascular medications amongst individuals in whom these treatments are indicated. Trial Registration This trial is registered with the Australian New Zealand Clinical Trial Registry ACTRN126080005833347.